Who's prone to drone? A global time-series analysis of armed uninhabited aerial vehicle proliferation. (March 2022) - Horowitz, Michael; Schwartz, Joshua A; Fuhrmann, Matthew
What determines whether countries pursue and obtain armed drones? Using an original time-series dataset, we conduct the first comprehensive analysis of armed drone proliferation from 1994 to 2019. We theorize and find evidence that security threats—like terrorism—are not the only factors driving proliferation. Regime type also has a significant effect, but it varies over time. From 1994 to 2010 regime type had no significant effect. However, non-democracies became significantly more likely to pursue and obtain armed drones from 2011 to 2019 owing to China's entrance into the drone export market, which asymmetrically eased supply-side constraints for non-democracies. We also find that status-seeking states are more likely to pursue armed drones. Our results contribute to the broader academic literature on proliferation by demonstrating how supply shocks can lead to changes in proliferation trends over time and lending further credence to the importance of prestige in international politics.